Shrub encroachment alters plant trait response to nitrogen addition in a semi-arid grassland - Li, Dan; Liu, Yanshu; Yang, Xiaohui; Zhang, Xiao; Shi, Zhongjie (Frontiers in Plant Science, 2023)
Large regions of arid and semi-arid grassland have been encroached upon by shrubs, which can affect grass traits and the growth of the original steppe, which nitrogen (N) enrichment generally promotes. However, the effects of N input gradients on the growth of grassland species growth and the traits of grasslands encroached by shrubs remain unclear. Here we examined the effects of six different N addition rates on the growth and traits of Leymus chinensis in an Inner Mongolia grassland, which was encroached by Caragana microphylla (legume). We randomly selected 20 healthy tillers of L. chinensis under and between the shrub patches in each plot, measuring the plant height, number of plant leaves, leaf area, LNCmass, and aboveground biomass. Our results showed that N addition significantly enhanced the LNCmass of L. chinensis. The aboveground biomass, heights, LNCmass, leaf areas, and number of leaves under the shrubs were higher than those between them. For the L. chinensis between shrubs, the LNCmass and leaf area, number of leaves, and height increased with N addition rates, reaching a maximum value at 10g N·m-2·yr-1, then decreased. However, the number of leaves, leaf areas, and heights under the shrubs did not vary between N addition rates. These results indicated that shrub encroachment and N input gradients have complex interactions for plant growth and the traits of original grasslands. This study provides new insights into the role of biotic interactions on grasslands in the context of N deposition.